2012
DOI: 10.1044/1092-4388(2011/10-0298)
|View full text |Cite
|
Sign up to set email alerts
|

Shared-Reading Dynamics: Mothers' Question Use and the Verbal Participation of Children With Specific Language Impairment

Abstract: The findings were contrary to hypotheses and collectively suggest potentially unique and challenging verbal dynamics between mothers and their young children with SLI during shared-reading experiences. Future directions for research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
2
24
1
1
Order By: Relevance
“…Although wh ‐ questions have been the focus of prior work (Lee et al., ; Leech et al., ; McGinty et al., ), we did not find that inferential wh ‐ questions predicted children's vocabulary growth. Future replication of our work is needed before a definitive conclusion can be made regarding which type of inferential utterance best promotes children's vocabulary.…”
Section: Practical Importancecontrasting
confidence: 91%
See 1 more Smart Citation
“…Although wh ‐ questions have been the focus of prior work (Lee et al., ; Leech et al., ; McGinty et al., ), we did not find that inferential wh ‐ questions predicted children's vocabulary growth. Future replication of our work is needed before a definitive conclusion can be made regarding which type of inferential utterance best promotes children's vocabulary.…”
Section: Practical Importancecontrasting
confidence: 91%
“…The current study was also limited to only one mother–child storybook observation. Although this is common in the literature on parents’ extratextual utterances (e.g., Fletcher et al., ; Hammett et al., ; Hindman et al., ; Kang et al., ; McGinty et al., ), it is not clear how representative this one book‐reading session is of typical mother–child interactions. However, other researchers have found that parents’ and teachers’ inferential talk to young children during a single book‐reading observation predicts children's later language skills (e.g., Hindman et al., ).…”
Section: Limitationsmentioning
confidence: 99%
“…Pour finir, bien que l'âge des enfants, le « statut » de l'adulte mais aussi, comme l'ont souligné Danis et al (2000) et McGinty et al (2012), les comportements et les conduites discursives des enfants, semblent influer sur les conduites discursives des mères et des enseignants, il semblerait également qu'il existe des variabilités individuelles qui puissent se regrouper en fonction de profils communs, comme l'ont remarqué Salazar Orvig et de Weck (à paraître), indépendants des premiers facteurs. Les enfants sont donc confrontés, tout au long de leur scolarité à l'école maternelle, à différents styles de conduites et d'expériences discursives qui leur permettront in fine de construire seuls des récits.…”
Section: Resultsunclassified
“…They may also be concerned that asking questions of greater cognitive challenge may not promote linguistically complex responses (e.g. McGinty et al, 2012). This may also aid in determining appropriate guidelines for frequencies of questions.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%